2014
DOI: 10.1371/journal.pone.0091747
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lipolysis Stimulated Lipoprotein Receptor in Breast Cancer and Directing Breast Cancer Cell Behavior

Abstract: The claudin-low molecular subtype of breast cancer is of particular interest for clinically the majority of these tumors are poor prognosis, triple negative, invasive ductal carcinomas. Claudin-low tumors are characterized by cancer stem cell-like features and low expression of cell junction and adhesion proteins. Herein, we sought to define the role of lipolysis stimulated lipoprotein receptor (LSR) in breast cancer and cancer cell behavior as LSR was recently correlated with tumor-initiating features. We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 38 publications
2
48
0
Order By: Relevance
“…For example, over-expression of LSR enhances cell proliferation and migration, as well as stimulates cancer-stem cell related properties such as survival in anchorage-independent conditions [21]. We also show that LSR expression significantly correlates with ERα expression in primary breast cancer biopsies [21]. In the current study, we show that tamoxifen-resistant breast cancer cell lines also express LSR and are sensitive to iota toxin-induced cytotoxicity.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…For example, over-expression of LSR enhances cell proliferation and migration, as well as stimulates cancer-stem cell related properties such as survival in anchorage-independent conditions [21]. We also show that LSR expression significantly correlates with ERα expression in primary breast cancer biopsies [21]. In the current study, we show that tamoxifen-resistant breast cancer cell lines also express LSR and are sensitive to iota toxin-induced cytotoxicity.…”
Section: Discussionsupporting
confidence: 62%
“…However, an emerging problem has been that ~33% of patients given tamoxifen therapy for five years develop recurrent tumors, and of those, 26% subsequently die [49-51]. Previous studies in our laboratory show that LSR is positively correlated with ERα expression [21]. Tamoxifen-resistant breast cancers are derived from ERα-positive tumors, and thus are likely to have high expression of LSR making them potential candidates for successful treatment with iota toxin.…”
Section: Resultsmentioning
confidence: 99%
“…TRIC expression is associated with Snail-induced EMT in gastric carcinoma cells and shows a negative correlation with the degree of differentiation in pancreatic ductal adenocarcinomas (13,14). The expression of the tTJ protein LSR may be associated with tumor progression and the degree of differentiation in addition to TRIC (16).…”
Section: Discussionmentioning
confidence: 97%
“…LSR signaling also promotes aggressive/tumor-initiating cell behaviors in breast cancer (16). In addition, our recent study revealed that small interfering RNA (siRNA)-mediated knockdown of LSR promoted cell invasion in human endometrial cancer cells.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, TRIC expression in gastric carcinoma cells is negatively regulated by snail-induced epithelial-mesenchymal transition (EMT)13. It is thought that the tTJ protein LSR is also associated with tumor progression14. Knockdown of LSR increases cell motility and invasion by bladder cancer cells15.…”
mentioning
confidence: 99%